Biaya Lingkungan dalam Laporan Keuangan Pemerintah: Tersembunyi, Terabaikan, atau Memang Tidak Terukur? - Aribah Muthi’ Choironi; Rina Tjandrakirana DP (GLOBAL SCIENTS PUBLISHER, 2026)
Environmental costs in government financial statements remain poorly understood despite their significance for public accountability. Using a Systematic Literature Review with PRISMA protocol, this study synthesizes 38 articles published between 2020 and 2026 to examine whether environmental costs are hidden, ignored, or unmeasurable. Findings reveal that all three conditions occur simultaneously and reinforce one another. Environmental costs are hidden through selective disclosure as a legitimacy management strategy, ignored due to path dependency and institutional inertia rather than mere technical incapacity, and deemed unmeasurable more as a social-institutional construction than an absolute technical limitation. Among developing countries including Indonesia, the